La representación de Mahoma: lo prohibido y lo permitido - Klein, Fernando (Nómadas. Critical Journal of Social and Juridical Science, 2008)
The article deals with the chances of illustration of Mohammed: is it forbidden to depict Mohammed in the Islam? What the history or the religion say about it? The following sentences try to get a brief but deep approaching to that issue, underlying the importance that just a few time ago (in the year 2006) when several problems related to misunderstanding and hatred set the Muslim world in front of the Western people as violent in a behavior that no one could share. Through the article we will see the lack of respect there was in some images that were published provoking all kind of reactions in the world.